Variabilidade espacial e manejo localizado de plantas daninhas em pomar de pereiras - Rodrigues, Samara (2009)
Weeds can negatively affect the quantity and quality on orchards fruit yield. They usually occur in clusters in a given area, not evenly distributed throughout the entire field. Thus, the site-specific application of herbicides makes possible the use of control methods, decreasing the entire cost. In this work, both spatial and temporal variability of broad-leafed and narrow-leafed weeds were evaluated in an orchard of pear trees, using tools of precision agriculture. The experimental area has 1.24 ha, cultivated with 146 pear trees (variety ―Pêra D água‖), located in Nova Laranjeiras, Paraná State, Brazil. The orchard s productivity was through two distinct harvests, given the different reaping point of its fruits. Eighteen pear trees were selected as reference for the four samplings of broad-leafed and narrow-leafed weeds populations, performed per tree, using a 0.5 m x 0.5 m (0.25 m2) wooden frame. Data collected were then used to elaborate maps of mean incidence from both types of weeds. The methodology used was efficient to quantify both types of weeds, since it allows to build maps of the spatial and temporal incidence of both types of plants (broad and narrow). Pear yield showed little correlation with weed incidence. The weeds showed spatial and temporal dependence and such dependence was different due to the leaf type (broad or narrow) and of the position (under the tree canopy or between lines). The western region showed the highest incidence of weeds in the experimental area.